Kepuasan Pemustaka Terhadap Layanan Perpustakaan Keliling Di Dinas Perpustakaan Dan Kearsipan Kota Bukittinggi - Pratama, Alvin Amanda; Primadesi, Yona (STKIP ROKANIA, 2023)
This study aims to describe: (1) Mobile Library Services at the Bukittinggi City Library and Archives Office given to Users, (2) User Satisfaction with Mobile Library Services at the Bukittinggi City Library and Archives Office. This type of research is qualitative with a descriptive method, informants in this study were selected using purposive sampling techniques. The data collection techniques carried out are observation, interviews, and documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusions. The results of this study show that: (1) Mobile library services at the Library and Archives Service can be carried out by users openly, services can be used by users to borrow collections and read in places with the reading garden provided, as well as for member registration, and for reading park services users are not allowed to bring books and are required to read in a place with the facilities provided, and for users who are not yet permanent members can also use mobile library services, so as to make it easier for users; (2) The satisfaction of users with mobile library services at the Bukittinggi City Library and Archives Department is good. The library has implemented the dimensions of Reliability, Responsiveness, Assurance, Empathy, and Physical Evidence. From the dimension of user satisfaction, based on the results of direct research to the field, everything can be fulfilled with a good response from users and user satisfaction with mobile library services can be fulfilled.